Influence of cimetidine on pharmacokinetics of propranolol. Issue 6280 (13th June 1981) - Heagerty, A M; Donovan, M A; Castleden, C M; Pohl, J F; Patel, L; Hedges, A
Abstract : Whole-blood propranolol concentrations were estimated for 12 hours after a single 80 mg oral dose was given in six patients taking cimetidine and two weeks after they had stopped the drug. Mean blood propranolol concentrations were higher throughout the sampling period when the patients were taking cimetidine than when they were not, and the difference was statistically significant between one and four hours (p less than 0.05). The mean relative bioavailability of propranolol, measured as the area under the concentration time curve, was significantly higher when the patients were taking cimetidine (p less than 0.025). The mean increase in bioavailability was 136.5 +/- 57.6%, and the results were consistent in each subject. It is concluded from these results that cimetidine reduces the hepatic first-pass extraction of propranolol.